Grand postcommunist narratives? - Kalnačs, Benedikts (Primerjalna književnost, 2015)
The article provides an insight into contemporary Latvian historical fiction. It focuses on a new series of historical novels, which aims at the interpretation of crucial transformations in the life of society during the 20th century. The first three novels in the series are discussed through a synchronic as well as a diachronic perspective. The introductory part of the article deals with recent general transformations in the literary scene in Latvia and with changes in the interpretation of history during the period of postcommunist transition in particular. A retrospective of the history of Latvian literature helps to explain the relevance of historical topics in the process of nation building. The novels under discussion are interpreted from the point of view of their literary genre and their use of time and space as constitutive factors in the creation of a literary text.
Keywords: Bankovskis, Pauls; Berzinš, Maris; književnost in zgodovina; latvijska književnost; narodotvornost; postkomunizem; prostor in čas; Zebris, Osvalds; zgodovinski roman